Pendampingan Pemasaran Melalui Digital Marketing Bagi Kelompok Tani Karya Bhakti Dalam Menghadapi Agrotechnopreneurship Millenial - Nursidiq, Cahyana; Lestari, Latifah; Yuniastanti, Linda; Lestari, Lia; Khusna, Vitrotul Amalia; Putri, Nanda Aktari Wahyu (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
A group is a group of people with a common goal who interact with each other to achieve a common goal, know each other, and see themselves as part of the group. Like the Karya Bhakti Farmer Group, which was established with the aim of strengthening the economy among its members. One of the ways that the farmer group uses to improve the economy of its members is by buying fertilizer taken from members which is then processed and traded. However, in the process of marketing their products, farmer groups only by word of mouth or often referred to as the Word Of Mouth (WOM) method which is less effective in increasing the sales volume of these fertilizer products. Therefore, the purpose of this research is to find the right method for marketing products by following existing technological advances. The method used in this research is a direct survey to the intended practicum site by directly interviewing trusted sources. From several surveys conducted, a solution to the existing problem was obtained, namely, to increase sales volume and expand the target market, it is necessary to do digital marketing through social media and choose the right sales method. Sales methods that support marketing through social media are electronic Word Of Mouth (e-WOM).